Respuesta :

Answer:

Step-by-step explanation:

x^2 - 10x + 29

x^2 - 10x = -29

x^2 -10x + 25 = -29 + 25

(x - 5)^2 = -4

(x - 5)^2 + 4 <==

The equation x² - 10x + 29 can be rearranged and represented by the function (x - 5)² + 4

What is an equation?

An equation is an expression that shows the relationship between two or more numbers and variables.

Given the function:

x² - 10x + 29

Adding and subtracting 25 to the equation:

x² - 10x + 25 + 29 - 25

(x - 5)² + 4

The equation x² - 10x + 29 can be rearranged and represented by the function (x - 5)² + 4

Find out more on equation at: https://brainly.com/question/2972832